The soldier and the scientist - Kapur, Brig. B.D. (Defence Science Journal, 2013)
To an average soldier the very name of a scientist conjures up strange visions of grey haired old gentleman who spend their lives in back cellars bending over flasks and tubes looking for things which are not there, their brain brimming with ideas, their enthusiasm always worked up to a high pitch. To a scientist the modern soldier is no less intriguing when he realizes the complexity of the modern army, which uses intricate weapons. The soldier makes a demand on the scientist who not only satisfies this demand by producing a machine which is simple to operate but even suggests to the soldier the possible developments that may help to achieve nation